2014
DOI: 10.3390/rs61211753
|View full text |Cite
|
Sign up to set email alerts
|

On-Orbit Radiometric Performance of the Landsat 8 Thermal Infrared Sensor

Abstract: The Thermal Infrared Sensor (TIRS) requirements for noise, stability, and uniformity were designed to ensure the radiometric integrity of the data products. Since the launch of Landsat 8 in February 2013, many of these evaluations have been based on routine measurements of the onboard calibration sources, which include a variable-temperature blackbody and a deep space view port. The noise equivalent change in temperature (NEdT) of TIRS data is approximately 0.05 K @ 300 K in both bands, exceeding requirements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 6 publications
0
36
0
1
Order By: Relevance
“…All indications from this dataset are that the TIRS instrument is thermally and electrically stable [2]. There have been, however, two anomalies that have been observed that require further investigation.…”
Section: Current Statusmentioning
confidence: 98%
See 4 more Smart Citations
“…All indications from this dataset are that the TIRS instrument is thermally and electrically stable [2]. There have been, however, two anomalies that have been observed that require further investigation.…”
Section: Current Statusmentioning
confidence: 98%
“…The image data from the OBC are used to monitor the stability of the radiometric response of the instrument. The OBC is normally fixed around 295 K, but can be set to temperatures from roughly 270 K to 320 K. The stability of the background and dark signals, as well as the response stability to the OBC are continuously monitored on-orbit [2].…”
Section: On-orbit Operation and Post-launch Adjustmentsmentioning
confidence: 99%
See 3 more Smart Citations